Uporaba metode premičnih najmanjših kvadratov za gladko aproksimacijo vzorčnih podatkov - Grešovnik, Igor (Strojniški vestnik, 2007)
The use of the moving least-squares approximation for the smoothing of data and the approximation of noisy response functions is presented. The approximation properties are treated with respect to the level of noise, the sampling density and the effective range of the sample. The applicability of the method is demonstrated by smoothing experimental measurement data and solving an optimization problem with a noisy response by the successive response approximation technique. The results indicate that the moving least-squares approximation is applicable to a wide variety of problems due toits smoothness, its accurate approximation over arbitrarily large domains using low-order basis functions, its ability to deal with an irregular arrangement of sampling points and to adapt to different modes of the approximation function in different regions.
Keywords: metoda premičnih najmanjših kvadratov; aproksimacija; glajenje; optimiranje; vzorčenje